Apresentação Dossiê : Ensino de Ciências e Formação de professores: olhares contemporâneos - Busato Zandavalli, Carla; Correa, Daniele; de Affonseca Jardim, Maria Inês; Sandalo Pereira, Patrícia (INTERFACES DA EDUCAÇÃO, 2024)
_